Determinan Kematian Maternal di Kabupaten Tangerang Tahun 2018-2019 - Happy Novriyanti Purwadi; hanny Desmiati; Nuntarsih Nuntarsih (Indonesian Journal of Midwifery (IJM), 2021)
Based on data from the SDKI, the Maternal Mortality Rate (MMR) in Indonesia is still quite high, namely 359 per 100,000 live births1, and the results of the Inter-Census Population Survey show a decrease to 305 per 100,0002, this result is still quite far considering the Sustainable Development Goals (SDGs) target, namely reduce maternal mortality to below 70 per 100,000 target by 20303. The diversity of causes of maternal mortality and differences in regional characteristics make it necessary to make policies and plans to reduce MMR. AKI is an indicator of maternal health status. McCharty and Maine suggest 3 factors that influence maternal mortality, namely the near determinant, the intermediate determinant and the distant determinant.This research uses analytical research method, using secondary data, this method was chosen because in the first stage research will be conducted on the determinants of maternal mortality, then in the second stage an analysis will be carried out (analytic) to determine the determinants that have the most influence on maternal mortality in Tangerang Regency.There is a relationship between parity and maternal mortality with a p value of 0.025; OR = 5.667, which means that parity has 5.6 times the maternal mortality. There is a relationship between Ante Natal Care (ANC) examination and maternal mortality with a p value of 0.004; OR = 8,889 which means that ANC examination has 8.8 times of maternal mortality. There is a relationship between complications and maternal death with a p value of 0.019; OR = 7.5, which means that complications have 7.5 times the death rate and husband's work with maternal mortality p value 0.035; OR = 0.117. Thus parity, ANC examination, complications and husband's occupation have an effect on the determinants of maternal mortality.Â